Etiology of viral respiratory infections in Northern Lao People's Democratic Republic - Chantal J. Snoeck (2018)
© 2018 Wiley Periodicals, Inc. In Lao People's Democratic Republic (PDR), acute respiratory infections overburden the health care system, but viral etiology, genetic diversity, and seasonality, especially in light of the introduction of influenza vaccination in the country, are poorly understood. From August 2010 to April 2011, 309 outpatients were recruited at the Luang Prabang Provincial Hospital covering highland Lao communities. Nasopharyngeal swabs were screened for the presence of 13 respiratory viruses. At least one virus was detected in 69.6% and dual/triple viral infections in 12.9%/1.9% of the patients. Influenza A and B viruses combined were the most frequently detected pathogens, followed by human adenovirus and respiratory syncytial virus (RSV). The other viruses were detected in less than 10% of the patients. Phylogenetic analyses on a representative set of RSV strains revealed that, while otherwise very rare, the RSV-B CB1/THB genotype cocirculated with other common genotypes. A single wave of influenza virus and RSV activity was observed during the rainy season, providing further support to influenza vaccination before the onset of the rains. This study provides recommendations for influenza vaccination that still needs optimization and highlights the need for revised guidelines for treatment and prevention of respiratory infections in Lao PDR, as well as for increased surveillance efforts.